Globalization and financial sector's net-interest margins: do specialization and ownership make a difference? - Sufian, Fadzlan (Taylor & Francis, 2012)
The impact of globalization on the well-being of the economy has been widely documented in the literature. Noticeably absent is empirical evidence on the impact of globalization on financial sector’s net-interest margins (NIMs). This limitation is somewhat surprising, given the fact that the financial sector remains the most important channel for savings and allocations of credit. By using the data on Malaysian financial institutions, this paper attempts to fill this demanding gap. The research has found that greater economic integration via higher trade flows, cultural proximity, and political globalization have a significant and negative influence on Malaysian financial institutions’ NIMs. The impacts of personal contacts and information flows seem to work in favour of Malaysian financial institutions. During the period under study, the researchers found that liberalization (restrictions) of the capital account exerts a negative (positive) influence on Malaysian financial institutions’ NIMs. However, the impacts are not uniform across financial institutions of different specializations and ownership structures.